2022
DOI: 10.1177/03611981221077085
|View full text |Cite
|
Sign up to set email alerts
|

Car-Following Properties of a Commercial Adaptive Cruise Control System: A Pilot Field Test

Abstract: Automated driving systems, which can take over certain dynamic driving tasks from the driver, are becoming increasingly available in commercial vehicles. One of these automated driving systems widely introduced in commercial vehicles is adaptive cruise control (ACC). This system is designed to maintain certain desired driving speeds and time headways as chosen by drivers and based on the settings available within the system. The properties and actual performance of these systems will affect the traffic flow an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
8
2
Order By: Relevance
“…The maximum acceleration is about 2.02 m/s 2 , which is lower than the value assumed for AVs in Niels et al ( 19 ) (3.0 m/s 2 ), but higher than the upper acceleration for AV in Şentürk Berktaş and Tanyel ( 12 ) (1.4 m/s 2 ). The starting response time to green light of HDVs is 0.70 s, which is slightly shorter than Clement et al ( 17 ) and Abraham ( 20 ), which reported values between 0.8 and 0.9 s. Contrary to the much shorter response time expected in the literature ( 19 , 13 , 20 ), it is 1.01 s for AVs which is comparable to or slightly longer than HDVs ( 6 ). In addition, some HDVs have a response time that is shorter than 0 s, meaning that they anticipate the green light and tend to react before the light turns green.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The maximum acceleration is about 2.02 m/s 2 , which is lower than the value assumed for AVs in Niels et al ( 19 ) (3.0 m/s 2 ), but higher than the upper acceleration for AV in Şentürk Berktaş and Tanyel ( 12 ) (1.4 m/s 2 ). The starting response time to green light of HDVs is 0.70 s, which is slightly shorter than Clement et al ( 17 ) and Abraham ( 20 ), which reported values between 0.8 and 0.9 s. Contrary to the much shorter response time expected in the literature ( 19 , 13 , 20 ), it is 1.01 s for AVs which is comparable to or slightly longer than HDVs ( 6 ). In addition, some HDVs have a response time that is shorter than 0 s, meaning that they anticipate the green light and tend to react before the light turns green.…”
Section: Discussioncontrasting
confidence: 53%
“…There are also some studies that directly investigated driving behavior of the adaptive cruise control (ACC) system when interacting with HDVs. For instance, Raju et al ( 6 ) tested the real performance of a commercial ACC system under different desired speeds in a car-following situation, and found that the system response times were not instantaneous but were rather comparable to human response times. Li et al ( 5 ) characterized car-following behavior of ACC vehicles based on empirical experiments, and explained the behaviors underlying mechanisms, such as factors influencing the response time, oscillation growth, and overshoot.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, the shortest gap setting (setting 1) for all vehicles' ACCs has been applied to investigate driving safety marginal levels through analyzing distance gaps between each of the two following vehicles. This is also the procedure conducted by [27,34] as they indicated that long-distance gap settings leads to frequent cut-in situations by other vehicles. The first exploration of the empirical works revealed that at low and medium speed ranges, all ACC systems show plausible following distances that maintain sufficient precollision braking distance in case the preceding vehicle applied brakes suddenly.…”
Section: Discussionmentioning
confidence: 92%
“…The results of the study revealed that all of the ACC systems in the seven vehicle models tested were string unstable. Raju et al [27] have conducted field tests using two commercial vehicles equipped with ACC, in which the following vehicle tracked the leading vehicle's pace when the ACC system was activated to assess its real-world functionality. The results suggest that different system speed and gap settings have an impact on the indicators for car-following, and the system's response times were observed to be on par with human response times.…”
Section: Introductionmentioning
confidence: 99%